The Effect of Fermented Coffee Husk on The Growth Performance of Biromaru Kampung Chicken - Ramadan, Farham; Teguh, Muhammad; Saifullah, Saifullah; Pratama, Tegar; Zam, Nurul Azmi (Universitas Bengkulu, 2025)
This study aimed to determine the effect of providing fermented coffee husk waste on the growth performance of Biromaru Kampung chickens. The high price of conventional feed has led to the exploration of more economical alternatives, one of which is the utilisation of agricultural waste, such as coffee waste. The nutritional value of coffee husk waste can be increased and its antinutrient content reduced through fermentation using microorganisms. The study was carried out for six weeks in Palu, Central Sulawesi, using a Completely Randomized Design (CRD) consisting of four treatments and five replications: P0 (basal feed), P1 (90% P0 + 10% non-fermented coffee waste), P2 (90% P0 + 10% fermented coffee waste with Saccharomyces cerevisiae), and P3 (90% P0 + 10% fermented coffee waste with Effective Microorganisms 4). Feed consumption, body weight gain, and feed conversion ratio were measured as the variables of interest. The results indicated that feed consumption was significantly increased in treatments P1 and P3, while body weight gain and feed conversion ratio were not significantly affected. Providing fermented coffee waste as an alternative feed for Biromaru Kampung chickens resulted in a significant increase in feed consumption, particularly in treatments P1 (10% non-fermented coffee waste) and P3 (10% fermented coffee waste with Effective Microorganisms 4). Although body weight gain did not differ significantly between treatments, there was a tendency for an increase in P1 and P3. Additionally, treatment P3 demonstrated the best feed conversion efficiency compared to the other treatments. Overall, fermented coffee husk waste has the potential to increase feed consumption and efficiency. However, its impact on body weight gain still needs further research to understand the mechanism of its influence in more depth.